2018
DOI: 10.2355/isijinternational.isijint-2017-356
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Solidification Pressure on Interfacial Heat Transfer and Solidification Structure of 19Cr14Mn0.9N High Nitrogen Steel

Abstract: The effect of solidification pressure (0.5, 0.85 and 1.2 MPa) on heat transfer between ingot and mould was investigated with the measurement of cooling curves and calculation of heat transfer coefficient. Combined with cooling rate, temperature gradient and local solidification time (LST), the influence of pressure on solidification structure of 19Cr14Mn0.9N was revealed by macrostructure observation. The calculation results of heat transfer coefficient, obtained by the Beck-Nonlinear estimation technique, ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Local solidification time ( LST ) is a decisive factor for the solidification structure during the ESR process, and it can be calculated by Equation LST=XnormalM/v1=XnormalM/true(vsnormalcosθtrue) where X M is the distance between solidus and liquidus, v l is the local solidification velocity and perpendicular to the solidus carve, v s is the velocity of withdrawing and can be obtained by calculating the remelting rate and θ is the angle for solidification front and axial.…”
Section: Discussionmentioning
confidence: 99%
“…Local solidification time ( LST ) is a decisive factor for the solidification structure during the ESR process, and it can be calculated by Equation LST=XnormalM/v1=XnormalM/true(vsnormalcosθtrue) where X M is the distance between solidus and liquidus, v l is the local solidification velocity and perpendicular to the solidus carve, v s is the velocity of withdrawing and can be obtained by calculating the remelting rate and θ is the angle for solidification front and axial.…”
Section: Discussionmentioning
confidence: 99%
“…The increment of pressure can speed up the reaction rate, improve the cooling rate, refine the solidification structure and eliminate the solidification defects, etc. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] In addition, increasing pressure can effectively refine carbides to alleviate the negative effect. Li 16) increases pressure and higher solidification pressure is beneficial to reduce the volume fraction of M 6 C. Therefore, it is worth exploring a new method to improve quality of H13 ingot using the pressurized metallurgy technology.…”
Section: Effect Of Pressure On Dendrite Structure and Characteristics Of Carbides During Solidification Process Of H13 Die Steel Ingotmentioning
confidence: 99%
“…It is well established that the relation between dendrite arm spacing and cooling rate is crucial to investigate the effect of pressure on dendrite structure. 17) The relation between the SDAS λ 2 and cooling rate R can be written as follow: 32,33) where n and M, mainly depending on alloy compositions, can be regarded as constant. 32,33) Curves represented the quantitative correlation between λ 2 and R (the cooling rate is between 0.5 and 3 K/s) were fitted as shown in Fig.…”
Section: Effect Of Pressure On Dendrite Structurementioning
confidence: 99%
“…8,9) In addition, pressure also affects the solidification process. 10) On the one hand, increasing pressure could decrease the heat resistance at ingot/mould interface and enhance the cooling rate of ingots, providing a fine solidification structure. [11][12][13][14] On the other hand, increasing pressure could affect the thermodynamic and kinetic parameters, and change the solidification mode.…”
Section: Effects Of Nitrogen Gas Pressure On the Solidification Parammentioning
confidence: 99%
“…Meanwhile, the Q loss increases with an increase in pressure because increasing pressure could decrease the air gap. [10][11][12][13][14] However, the pool depth increased from 28 to 34 mm. This indicated that there was also an increase in the heat transfer rate at the slag/pool interface.…”
Section: Effects Of Nitrogen Gas Pressure On Solidificationmentioning
confidence: 99%